Integrated Learning Model Training (Blegur Model) as an Innovative Strategy to Strengthen Students' 21st-Century Learning - Jusuf Blegur; Zuvyati Aryani Tlonaen; Intan Christine Adriani Siki (Borneo Research and Education Center, 2026)
The Integrated Learning Model (Blegur Model) is a new model that can be applied to improve students' 21st-century competencies because it organizes student learning experiences around objectives, analytical thinking, integrity, and transformation. However, students' understanding and skills in implementing this learning model are still limited because it is relatively new, so systematic intervention is needed. This community service program is designed to improve students' understanding and skills in applying the Blegur Model. This innovative alternative combines aspects of analysis, evaluation, and the implementation of learning. The activity involved 15 students, but only 13 students (86.67%) completed the pre-test and post-test. The materials provided included theoretical foundations, the significance of the Blegur Model for 21st-century competencies, comparisons with other learning models, and syntax and implementation strategies. The training was carried out through three main methods: lectures and discussions, model application exercises, and presentations and reflections. Evaluation was carried out using four open-ended questions with an assessment rubric, which participants collected through presentation videos in the pre-test and post-test. Data analysis using descriptive statistics and the Wilcoxon signed-rank test showed a significant increase in participants' understanding and skills (Z = -3.395; p = 0.001; r = 0.94). These training results confirm the effectiveness of the Blegur Model as an innovative learning strategy that can strengthen students' competencies and support the development of learning practices aligned with the demands of the 21st century.